Ostrich boys - Gray, Keith (London : Definitions in association with the Bodley Head, 2008)
After their best friend Ross dies, English teenagers Blake, Kenny, and Sim plan a proper memorial by taking his ashes to Ross, Scotland, an adventure-filled journey that tests their loyalty to each other and forces them to question what friendship means.
Keywords: Death -- Fiction; Friendship -- Fiction; England -- Fiction; Scotland -- Fiction